What do we really know about fiscal sustainability in the EU? A panel data diagnostic - António Afonso; Christophe Rault (European Central Bank (ECB), 2007)
We assess the sustainability of public finances in the EU15 over the period 1970-2006 using stationarity and cointegration analysis. Specifically, we use panel unit root tests of the first and second generation allowing in some cases for structural breaks. We also apply modern panel cointegration techniques developed by Pedroni (1999, 2004), generalized by Banerjee and Carrion-i-Silvestre (2006) and Westerlund and Edgerton (2007), to a structural long-run equation between general government expenditures and revenues. While estimations point to fiscal sustainability being an issue in some countries, fiscal policy was sustainable both for the EU15 panel set, and within subperiods (1970-1991 and 1992-2006).
Keywords: C23; E62; H62; H63; 330; EU; Fiscal sustainability; intertemporal budget constraint; panel cointegration; panel unit root; Finanzpolitik; Budgetrestriktion; Liquiditätsbeschränkung; Europäischer Stabilitätsmechanismus; Geldpolitik; Eurozone; EU-Staaten